Disability in the national censuses of 2002 and 2011 – a comparison of information scope - Dehnel, Grażyna; Klimanek, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Data on disability are collected in many statistical surveys, but the largest ones are censuses. The survey of disability based on census data in Poland has a long history dating back to 1921. During this period both the methodology of the survey and the scope of the data have been changing. The biggest modifications took place in 2011. NCP 2011 was the first census in Poland to be carried out by combing administrative data sources and the survey sampling method. The aim of the present study is to analyze and assess changes in the disability survey in NCP 2011 compared to NCP 2002 in terms of methodology and the scope of information.